Spatial Directions for the Malino Nature Tourism Park in Gowa Regency - Firdaus; Didiet Haryadi Hakim (PT FORMOSA CENDEKIA GLOBAL, 2023)
The implementation of spatial planning as stipulated in Law Number 26 of 2007 concerning Spatial Planning mandates the need to carry out spatial planning that can harmonize the natural environment and the artificial environment which is able to realize the integration of the use of natural resources and artificial resources. The potential threat to the sustainability of this Nature Tourism Park is the development of cultivation activities and also forest encroachment. Therefore, it is necessary to carry out spatial directions for the Malino nature tourism park area in Gowa Regency. The aims of this research are to define area boundaries, determine regional strategic values and issues, determine the condition of disaster-prone areas and explain tourism carrying capacity. The methodology is carried out by collecting data related to problems obtained from books as well as standards and regulations. The results of this study found that the main issues that need to be prioritized in regional planning are tourism and spatial planning, areas with high potential are found in parts of Bulutana and Bontolerung Villages, the maximum number of tourists that can be accommodated by the Pinus Malino Tourism Forest area without damaging the ecosystem and can be served by both by officers as many as 372 tourists per day and efforts to increase the number of tourists with all their activities properly when the actual number of tourists does not exceed the maximum limit